Bridging awareness and action in flood risk reduction: Insights from a community-based evaluation - Kurniawan, Madeleine Beatrice; Maulana, Razin Akmal; Arifin, Jisca Atiqah; Anthonius, Ferdy; Kurniawan, Markus (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Flooding is a disaster that continues to be faced by Indonesia. Every year, floods inevitably occur. From year to year, the number of floods continues to increase. This is why we conducted a study on residents’ knowledge regarding flood prevention in their environment. Methods: This research aims to evaluate the knowledge of Tomang residents about flood prevention methods using a qualitative approach, employing semi-structured interviews and observation techniques. Findings: Through this process, the research findings show that the people of Tomang possess varying levels of knowledge regarding flood prevention. Most residents are already aware of the importance of maintaining drainage systems and managing waste, although they face various challenges in fully implementing these preventive measures. Conclusion: The results of this study indicate that more intensive education and outreach, along with greater involvement and active participation of the community in flood prevention programs, can help prevent flood disasters in the area. Based on these findings, we hope that this information can serve as a foundation for flood prevention and risk reduction at the local level. Novelty/Originality of this article: The novelty/originality of this article lies in evaluating Tomang residents’ knowledge of flood prevention using a qualitative approach, revealing implementation gaps despite their relatively good awareness.